Business in practice: analysis of the strategic change of an automobile manufacturer and self-reflection on the journey - Fehr, Tobias (2024)
The Business in Practice (BiP) program focuses on an immersive business simulation that combines academic concepts with practical applications. Students work in teams to manage a global automotive company, tackling real-world challenges such as the transition to electric vehicles and the integration of sustainability. The program emphasizes the strategic interplay of key business functions – finance, operations, marketing, innovation, and human resources. In addition, participants develop key skills in team dynamics and leadership as they develop and implement long-term business strategies. This thesis focuses on analyzing the company’s performance during the simulation and reflecting on personal development.